2009
DOI: 10.1209/0295-5075/87/40007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the transition from ordered to disordered growth during rapid solidification of an intermetallic phase

Abstract: The dendrite growth velocity during solidification is measured on liquid drops of the intermetallic compound Ni50Al50 undercooled by levitation up to 265 K. A sharp increase of the growth velocity is found at a critical undercooling ∆T * ≈ 250 K. In situ diffraction of synchrotron radiation on levitation-processed samples unambiguously shows a transition from ordered to disordered growth at ∆T * . The sharp interface model is extended to describe the transition from ordered to disordered dendrite growth by tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 24 publications
5
31
0
Order By: Relevance
“…This is perhaps not surprising given the very low post-recalescence coolig rates that can be achieved during melt fluxing (typically of order 10 K s -1 ) due to the high thermal mass of the flux, crucible, susceptor and heat shield relative to that of the sample. This would be consistent with in situ energy dispersive X-ray diffraction studies using synchrotron radiation on levitation undercooled Ni-Al which revealed that disordered superlattice structures can recrystallise to the ordered state on timescales of only a few seconds [29]. 3 Ge is an ordered intermetallic compound displaying congruent melting in the composition range 22.5-25.0 at.% Ge.…”
Section: Resultssupporting
confidence: 83%
“…This is perhaps not surprising given the very low post-recalescence coolig rates that can be achieved during melt fluxing (typically of order 10 K s -1 ) due to the high thermal mass of the flux, crucible, susceptor and heat shield relative to that of the sample. This would be consistent with in situ energy dispersive X-ray diffraction studies using synchrotron radiation on levitation undercooled Ni-Al which revealed that disordered superlattice structures can recrystallise to the ordered state on timescales of only a few seconds [29]. 3 Ge is an ordered intermetallic compound displaying congruent melting in the composition range 22.5-25.0 at.% Ge.…”
Section: Resultssupporting
confidence: 83%
“…From this kinetic phase diagram, the kinetic undercooling ∆T K (difference between local equilibrium liquidus and velocity dependent liquidus temperature), k(V) and m(V) are directly inferred. More details of the computations are given in [64]. The results of the computations of dendrite growth velocity as a function of undercooling are given in the upper part of Figure 12 (solid line).…”
Section: Disorder Trapping and Disordered Superlattice Structurementioning
confidence: 99%
“…Since the transition from disordered to ordered phase takes place rapidly [59], a primarily formed disordered B2 phase is not necessarily present in the as solidified sample. In order to obtain unambiguous evidence of the formation of a metastable disordered phase during rapid solidification of the deeply undercooled melts Energy Dispersive X-ray Diffraction (EDXD) has been conducted on levitation processed Al 50 Ni 50 alloys using synchrotron radiation at the European Synchrotron Radiation Facility (ESRF) in Grenoble [64]. Figure 13 (left) shows the results of EDXD on a levitation processed Ni 50 Al 50 sample undercooled by 235 K prior to solidification.…”
Section: Disorder Trapping and Disordered Superlattice Structurementioning
confidence: 99%
“…If the undercooling increases, the non-equilibrium effect of disorder trapping leads to the formation of a metastable disordered structure. Experimental evidence of disorder trapping has been demonstrated by in situ diffraction studies using synchrotron radiation on levitation-processed samples, in which a transition from ordered to disordered growth at a critical undercooling was unambiguously shown [6]. The phenomenon of order-disorder transition with distinct change of the order parameter is also important in structural transformations with non-monotonic relaxation processes of melts [8] and in liquid-liquid phase separation of undercooled metallic alloys [9,10].…”
Section: Introductionmentioning
confidence: 96%
“…The disorder trapping was investigated from theoretic perspective by sharp interface models [2,3,6], a diffuse interface model [11] and methods of atomistic simulation [1,12]. In the present work, using an existing approach for fast phase transformations [13], a diffuse interface model results in a system of hyperbolic equations to describe (i) the rapid interface motion and (ii) the transition from ordered to disordered structures formed from undercooled liquids.…”
Section: Introductionmentioning
confidence: 99%